The Psychometric Properties of Adversity Quotient (AQ) Items for TVET Education using Rasch Model - Mohd Matore, Mohd Effendi @ Ewan bin; Khairani, Ahmad Zamri (Journal of Technical Education and Training, 2020)
Technical and Vocational Education Training (TVET) require technical students as knowledge workers who have specific intelligence to face the challenges namely Adversity Quotient (AQ). AQ is a measure of how the individual respond and deal with everything, from everyday difficulties to the huge adversities. The linkages of AQ items assessment towards technical students are inadequate in order to prepare them for the real industry job environment. Previous research stated that it has very limited universal instrument to measure AQ for technical students. This paper investigated the psychometric items quality in measuring AQ and to see the pattern of AQ among technical students in polytechnic focusing on mechanical engineering students using Rasch model. The research used survey with quantitative approach and involved 369 respondents using proportionate stratified multistage of cluster sampling. AQ was measured using four constructs of Control, Ownership, Reach and Endurance. The results revealed that 36 from 66 items are fulfilling the reliability and validity with considerations of item fit, unidimensionality, local independence, polarity item, Gender Differential Item Functioning and Wright Map. The pattern of AQ level showed 10.03% of the respondents are at the very high, 15.18% at a high level, 28.18% at the moderate high, 24.39% at the moderate low, 13.28% at the low level and 8.94 % at the very low level. The pattern of AQ was at the moderate level. The study may influence the implementation of AQ for technical students as a future TVET graduates in order to identify them in handling adversities. This pattern will provide new ideas in helping stake holders to strategize the programme implementations of AQ. The novelty is that the item produced was proven empirically be applicable in the context of polytechnic which is notable for mechanical engineering students.